Computational Thinking in Mathematics Learning Task Design: Stating Goal, Designing, and Plug In, of Indonesian Pre-service Math Teachers - N. Aminah; Y L Sukestiyarno; Wardono Wardono; A. N. Cahyono; D. R. Rozak; W. Kusriandi (International Conference on Science, Education, and Technology, 2021)
This study aims to describe the pedagogic knowledge of prospective mathematics teachers in making mathematics problem-solving problems with the concept of Computational Thinking (CT). This study uses an exploratory, descriptive quantitative research involving 95 prospective mathematics teacher students from various regions in Indonesia. The subject is given a job to design CT assignments in mathematics learning. Data obtained from performance sheets in the form of assignments made by prospective teachers. The data were analyzed using the question feasibility performance sheet due to design principles, the results of assignment-based interviews, and field notes. Data analysis was carried out by triangulation by combining the results of the analysis of performance sheets, interviews, and field notes, the results obtained from the performance of prospective teachers, design assignments by paying attention to design principles. Assignments are made accompanied by an answer key with concepts that support CT. In this case, the study results found the pedagogic knowledge of prospective mathematics teachers when making questions by paying attention to setting goals, designing, and plugin. There are significant differences in the criteria for each CT component seen from the level of knowledge of high, medium, low sig values of 0.000, respectively; 0.002; 0.004, and 0.008 means that there is a significant difference between each group.